2020
DOI: 10.1002/cam4.3369
|View full text |Cite
|
Sign up to set email alerts
|

Microarray profiling of differentially expressed lncRNAs and mRNAs in lung adenocarcinomas and bioinformatics analysis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…1 ). We further analyzed NK1R expression in NSCLC and adjacent non-tumor tissues in two datasets GSE130779 and GSE2514 downloaded from GEO databases [ 38 , 39 ], revealing that expression of NK1R was significantly upregulated in NSCLC tumor tissues compared with the adjacent non-tumor tissues or normal tissues (Fig. 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…1 ). We further analyzed NK1R expression in NSCLC and adjacent non-tumor tissues in two datasets GSE130779 and GSE2514 downloaded from GEO databases [ 38 , 39 ], revealing that expression of NK1R was significantly upregulated in NSCLC tumor tissues compared with the adjacent non-tumor tissues or normal tissues (Fig. 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…Tissue microarrays were performed as previously described. 23 Briefly, OPN antibody (1:200), vimentin antibody (1:100) and E‐cadherin antibody (1:100) were used to detect the protein expression of OPN, vimentin, and E‐cadherin. Additionally, the expression of OPN was semi‐quantitatively determined by two pathologists independently.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, LUAD and para-carcinoma tissue datasets were selected from the GEO database( https://www.ncbi.nlm.nih.gov/geo/ ). GSE85841 [ 33 ] (8 normal and 8 tumor samples) and GSE130779 [ 34 ] (8 normal and 8 tumor samples) were obtained. Results showed that logFC, logCPM, p value, and FDR of RIOX2 between the groups were 0.802107483, 3.681482308, 0.004666927, and 0.011185307, respectively.…”
Section: Resultsmentioning
confidence: 99%